Application of Concept Map Media to Improve Cognitive Learning OutcomesiIn Islamic Cultural History Subjects (Study at MI Attarbiyah) - Alby M Farisy Aminudin; Ahmad Basar; Endang Abdul Gopur; Euis Herlina; Uum Rohmatul Ummah; Dede Aji Mardani (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to determine the influence of concept map media on students' learning outcomes in the subject of SKI (History of Islamic Culture) in class VI at one of the Madrasah Ibtidaiyah schools in Tasikmalaya, where previously the learning process had not used concept map media. The research method used is quasi-experimental with a one group pretes-protest design design. The study population was 30 people in all class VI. The research instrument consisted of cognitive questions, 20 multiple choice questions for pretes and 20 multiple choice questions for postes whose validity and reliability had been tested. The results of this research show that when experimental classes were obtained, namely Spretes 69.33 and Spostes 78.83, the average experimental class N-Gain score was 0.29 and was included in the low category. With thitung > ttable analysis, H0 is rejected and H1 is accepted. This means that the changes obtained afterward are implemented by learning using the media of influential concept maps in the low category. Thus, it can be concluded that there is an influence with the implementation of the use of concept map learning media on students' learning outcomes in the SKI (History of Islamic Culture) subject.